Parents of Adolescents Perspectives of Physical Activity, Gaming and Virtual Reality: Qualitative Study - McMichael, Lucy (JMIR Serious Games, 2020)
BACKGROUND: Virtual reality (VR) exergaming may be a promising avenue to engage adolescents with physical activity. Since parental support is a consistent determinant of physical activity in adolescents, it is crucial to gather the views of parents of adolescents about this type of intervention. OBJECTIVE: This study aimed to interview parents of younger adolescents (13-17 years old) about physical activity, gaming, and VR as part of the larger vEngage study. METHODS: Semistructured interviews were conducted with 18 parents of adolescents. Data were synthesized using framework analysis. RESULTS: Parents believed that encouraging physical activity in adolescents was important, particularly for mental health. Most parents felt that their children were not active enough. Parents reported their adolescents regularly gamed, with mostly negative perceptions of gaming due to violent content and becoming addicted. Parents discussed an inability to relate to gaming due to “generational differences,” but an exception was exergaming, which they had played with their children in the past (eg, Wii Fit). Specific recommendations for promoting a VR exergaming intervention were provided, but ultimately parents strongly supported harnessing gaming for any positive purpose. CONCLUSIONS: The current study suggests promise for a VR exergaming intervention, but this must be framed in a way that addresses parental concerns, particularly around addiction, violence, and safety, without actively involving their participation. While parents would rather their children performed “real-world” physical activity, they believed the key to engagement was through technology. Overall, there was the perception that harnessing gaming and sedentary screen time for a positive purpose would be strongly supported.